Abstract Uneducated Injustice: A Social Cognitive Approach to Understanding Juror Misconduct and Verdict Errors - Calhoun, Melinee Melissa Marie (2015)
A continual problem in the adjudication of crime in the United States is the continued occurrence of erroneous convictions and acquittals. This problem impacts the victims of crimes as they endure emotional and mental distress of additional investigations and new trials. Defendants are impacted by errors in verdicts because of the loss of freedom while being factually innocent. These errors may occur because jurors may not be knowledgeable of their role, right and responsibilities. Without regard to the judge's minimum instruction, the jury is not provided direction on the purpose and limitations of their roles. Guided by the social cognitive theory, this correlational study examined the incorrect verdicts by jurors in 2 Georgia counties in order to evaluate whether pretrial training has an impact on the incidence of verdict error. An experimental design was used to evaluate the impact of juror training on the occurrence of erroneous convictions and acquittals. The study included 156 participants who were registered voters from Lowndes and Lanier County, Georgia. The variables training, verdict errors, and juror misconduct were analyzed using t test, Pearson correlation analysis, Levene's Test of Equality of Variances, and Chi square analysis. The findings indicated a significant inverse relationship between the administration of pre-trial training and the occurrence of verdict error. The results suggest a relationship between the occurrence of juror misconduct and erroneous convictions, which is consistent with impact of behavior on decision making as posited by SCT. The implications for positive social change include recommendations to Lowndes and Lanier County court administrators to consider routine pretrial training that includes information about the role of the juror in criminal trials